Evaluation of Degradation of Japanese Hanging Scrolls Using Relative Peak Area of Volatile Organic Compounds - Lee, Kang; Sablier, Michel; Enomae, Toshiharu; Inaba, Masamitsu (Studies in conservation, 2023)
Volatile organic compounds (VOCs) generated from naturally aged Japanese hanging scrolls and their model samples were measured using solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) to clarify the effect of different painting papers and raw materials on the degradation state of hanging scrolls. VOC-based degradation markers were identified and their applicability was considered for degradation evaluations of actual Japanese hanging scrolls. The relative peak areas of different VOC groups were calculated by normalising their peak areas to the total peak area of long-chain hydrocarbons. When a painting paper was immersed in a CuSO 4 ・5H 2 O solution, or coated with an alum solution, the relative peak areas of furfural and carboxylic acids increased after accelerated ageing, while these relative peak areas decreased when animal glue was applied, indicating that animal glue inhibited the generation of VOCs. When the painting paper containing Cu 2+ was stacked with lining paper, furfural and carboxylic acids migrated into the lining paper with ageing. Animal glue coated on the painting paper retarded this migration into the lining paper. For the lining paper coated with wheat starch paste, the relative peak areas of furfural, carboxylic acids, and aliphatic aldehydes did not change significantly with ageing, indicating that wheat starch paste did not contribute to paper degradation, although these relative peak areas increased when aged wheat starch paste was applied. These results indicate that the targeted VOCs are valid degradation markers of Japanese hanging scrolls.